The Role Of hs-CRP In Predicting The Likelihood Of Coronary Heart Disease (Indonesian Journal of Pharmaceutical and Clinical Research, 2020)
Coronary Heart Disease (CHD) is a disorder of the cardiovascular system, characterized by atherosclerotic lesions. Inflammation is a strong predictor for coronary heart disease. High sensitivity C-Reactive Protein (hs-CRP) is an important biomarker, synthesized in the liver, can predict the severity of CHD. If the hs-CRP level is found to be low 3 mg / L, a person has the potential for severe vascular risk. Therefore, hs-CRP can be used as a predictor of primary CHD prevention, especially if the hs-CRP level is still low.